Improving Creative Thinking Skills through Open-ended Problems in Mathematics Education in terms of Adversity Quotient (Types of Climbers and Campers) - Sa'idah, Ulya; Budiyono, Budiyono; Siswanto, Siswanto; Usodo, Budi; Hendriyanto, Agus (Universitas Muhammadiyah Mataram, 2024)
Creative thinking is one of the abilities that students must have. This research aims to explore creative thinking skills in solving open-ended problems in grade 7 students at a junior high school in Surakarta. This research uses a qualitative method. The instruments used are questionnaires, questions, and interviews. The test instrument uses one open-ended question on algebra material. The sampling method was carried out by purposive sampling where the subject was selected based on the results of the Adversity Response Profile (ARP) questionnaire score. The research subjects were 7th-grade students at one of Surakarta's private junior high schools who had studied algebraic form operations. Data were collected through tests and interviews with 4 research subjects. The data validity used was method triangulation. The results of the study show that all subjects can go through all stages of the creative thinking process although there are differences in each stage. In the preparation stage, climbers-type students do not need a long time to understand the problem. Unlike the campers, they take time to understand the problem by reading it repeatedly. At the incubation stage, students pause to look for ideas for solving the problem. At the illumination stage, students have different ways of solving the problem. At the verification stage, climbers-type students recalculate the answers written to check their correctness. While campers type students only skim the answers they write. Climbers-type students do not give up easily and do not experience difficulties in solving problems, while campers-type students take longer to understand the problem and almost give up in solving the problem. Based on the findings obtained, teachers need to consider the different types of students' creative thinking in designing class activities in order to improve students' creative thinking abilities through classroom learning.